2012
DOI: 10.1007/s10549-012-2197-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values of GHSR DNA methylation pattern in breast cancer

Abstract: DNA methylation patterns have been recognised as cancer-specific markers with high potential for clinical applications. We aimed at identifying methylation variations that differentiate between breast cancers and other breast tissue entities to establish a signature for diagnosis. Candidate genomic loci were analysed in 117 fresh-frozen breast specimens, which included cancer, benign and normal breast tissues from patients as well as material from healthy individuals. A cancer-specific DNA methylation signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…At cellular level, we observed a restoration of SFRP4 expression in pituitary adenoma cells (GH3) after treatment with the demethylating agent, 5-aza-2 V-deoxycytidine. These findings are consistent with studies conducted on various other malignancies, including gastric, cervical, hepatocellular, pancreatic, oral squamous cell, breast, colon, and bladder cancers (44)(45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 91%
“…At cellular level, we observed a restoration of SFRP4 expression in pituitary adenoma cells (GH3) after treatment with the demethylating agent, 5-aza-2 V-deoxycytidine. These findings are consistent with studies conducted on various other malignancies, including gastric, cervical, hepatocellular, pancreatic, oral squamous cell, breast, colon, and bladder cancers (44)(45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, expression of the cognate GHSR GHSR1a could even be reduced in breast cancer samples compared with normal mammary gland (Gahete et al 2011a). In line with this, it has been suggested that the hypermethylation of the GHSR promoter region could be the underlying cause of this phenomenon, as hypermethylation is a frequent hallmark observed in primary breast tumor (Ordway et al 2007) and its levels are negatively associated with GHSR1a expression (Botla et al 2012).…”
Section: Adrenal Tumorsmentioning
confidence: 88%
“…5 In an earlier study, we had found DNA hypermethylation in the promoter of the growth hormone secretagouge receptor (GHSR) gene as an epigenetic marker of highest accuracy for detection of breast cancer. 6 This finding was supported by analyzing tumors as well as an extensive list of control samples including normal-appearing tissue samples from cancer patients and healthy individuals, as well as benign lesions. The gene promoter was significantly hypermethylated in both invasive and non-invasive in situ ductal breast cancer as compared to other samples.…”
mentioning
confidence: 85%